Compositional features of cherts from the Jebel Zawa mines (Dohuk, Kurdistan Region of Iraq) and implications for exploitation strategies during the Late Chalcolithic/Early Bronze Age. (February 2020) - Moscone, D.; Eramo, G.; Caggiani, M.C.; Morandi Bonacossi, D.; Conati Barbaro, C.
Highlights: The Jebel Zawa chert mines occur in the Mid-Upper Eocene Pila Spi Fm (Kurdistan Region of Iraq) In situ production of large blades during the 4th to 3rd millennia BC. Primary chert samples from three valleys were analyzed following the NM-PCI protocol. Petrographic and Raman results highlight chert variability between the three valleys. Abstract: The aim of this paper is to present preliminary data on the composition of the Mid-Upper Eocene chert visible in massive outcrops in the Jebel Zawa valleys, in the Dohuk province of the Northern Kurdistan Region of Iraq. Large chert nodules were systematically extracted from open-air outcrops and natural karst galleries, and employed to produce large blades, known in literature as "Canaanean blades", from the end of 4th to the mid-3rd millennium BC. Knapping workshops have been identified, evidence of a complex technological organization which served to produce prepared cores and blades to be distributed in the region. Our work highlighted the statistical variability of chert composition at intra- and extra valley scales. The variables discussed in this study were determined by following an integrated multi-parametric protocol for chert characterization (NM-PCI) which includes macroscopic observation, microscopic description and chemical analyses performed with Raman micro-spectroscopy. The samples studied were collected in three valleys featuring mining activities. The Jebel Zawa mines are currently the only known mining complex in the Tigris region. The reference collection of data derived from this study will thus be of crucial importance in order to understand the exploitation strategies, time-frame and spread of Canaanean technology in the region during the urbanization phase.